Application of Component Criticality Importance Measures in Design Scheme of Power Plants - Smajo Bisanovic; Mersiha Samardzic; Damir Aganovic (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper presents application of component criticality importance measures in phase of preparation and design of power plants. These measures provide a numerical rank to determine which components are more important for power plant reliability improvement or more critical for power plant failure. Identifying critical components for power plant reliability provides an important input for decision-making and guidance throughout the development project. The study on several schematic design options of conventional thermal power plant show that the importance measures can be used as an effective tool to assess component criticality in the project phase of new production capacities.